PENGARUH TRANSPARANSI, AKUNTABILITAS, PENGAWASAN KEUANGAN DESA TERHADAP KINERJA PEMERINTAH DESA (Studi Kasus di Desa Majenang Sukodono Sragen) - Mayangsari Putri, Suharno & Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
Purpose for this investigation is to test for transparency effect, accountability and village supervision of finance to performancevillage’s government.This research was conducted at Sukodono Majenang village government with all population was 4085. Types of data used are qualitative data and quantitative data while resource are in use primary data and secondary data. Sampling technique using proportional area random sampling that is as much 94 people. Data collection method was done by using questionnaire and technical analysis using multiple liner regression analysis.The results of the stuy concluded that: 1) Transparency has a positive and significant effect on the performance of the village government of Sukodono Sragen, 2) Accountability has a positive and significant effect on the performance of the village government of Sukodono Sragen, 3) Supervision of Village Finance has a positive and significant effect on the performance of the village government of Sukodono Sragen.Keywords: Transpareny, accountability, supervision, performance.